2013
DOI: 10.1051/epjconf/20134105042
|View full text |Cite
|
Sign up to set email alerts
|

Wavepacket Splitting in the First 100 fs Determines the Products from the Bond Cleavage of Diphenylmethylchloride

Abstract: Abstract. An elementary chemical reaction proceeds through two distinct conical intersections. Benzhydryl radicals are formed with a delay of 80 fs, cations after 125 fs. The optical signal increases more slowly due to planarization and solvation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 6 publications
4
12
0
Order By: Relevance
“…The step in the rise of Ph 2 CH _ (blue line) at about 50% amplitude happens at 100 fs. In agreement with the observation for Ph 2 CH-Cl, where we observe such a step at 80 fs, 43 we assign this to the delayed generation of the radical. The excited state wavepacket propagates from the Franck-Condon region to a rst conical intersection that leads part of the wavepacket to the radical product.…”
Section: The Generation and Interconversion Of Benzhydryl Radicals Ansupporting
confidence: 91%
“…The step in the rise of Ph 2 CH _ (blue line) at about 50% amplitude happens at 100 fs. In agreement with the observation for Ph 2 CH-Cl, where we observe such a step at 80 fs, 43 we assign this to the delayed generation of the radical. The excited state wavepacket propagates from the Franck-Condon region to a rst conical intersection that leads part of the wavepacket to the radical product.…”
Section: The Generation and Interconversion Of Benzhydryl Radicals Ansupporting
confidence: 91%
“…At 67 fs, the radical yield starts to grow very rapidly as more and more parts of the wave packet couple through the three-state CoIn seam. This delay time is in very good agreement with the experimentally observed 76 fs 21 . The delay time of 143 fs for the ion pairs is only slightly longer than the measured one of 124 fs (Ref.…”
Section: Bond Cleavage Of Ph2ch–clsupporting
confidence: 90%
“…The initial bond cleavage is found to be mainly homolytic on the sub-hundred femtosecond time scale, while a small heterolytic fraction is slightly delayed 21 . In a previous theoretical study, a S 1 / S 0 CoIn was identified connecting the heterolytic and homolytic product channel, but two-dimensional QD simulations revealed that the wave packet does not reach the CoIn 22 .…”
Section: Bond Cleavage Of Ph2ch–clmentioning
confidence: 79%
See 1 more Smart Citation
“…The two lowest excited singlet states in the model system correspond to local π−π* transitions. Compared with other well-studied benzhydryl derivatives, 3,8,[10][11][12][13]19,22,24 the phosphonium leaving group offers a second chromophore and enhances the complexity of the excitation mechanism. Our calculations show that the excitation on the PH 2 Ph + moiety leads to the S 1 state, and the excitation on the PhCH 2 moiety leads to the S 2 state.…”
Section: Discussionmentioning
confidence: 99%